COOPERATIVE LEARNING AND PARTICIPATION IN GROUP WORKSHOPS ON IMPROVING DRAWING SKILLS-HOW INTERACTION CAN BE ENCOURAGED AMONG MIDDLE SCHOOL STUDENTS THROUGH THE USE OF INTEGRATION INTO SCHOOL WORKSHOPS AND GROUP EXERCISES - Karar Jamhour Mehdi Karmsh (Scholars Digest Publishing, 2024)
The research aims to shed light on the impact of cooperative learning and participation in group workshops to improve drawing skills, in addition to encouraging interaction between middle school students through the use of integration into school workshops and group exercises. The study relied on the experimental approach in the manner of the experimental and control groups and presented the theoretical concepts related to By describing the phenomenon, and collecting, analyzing and interpreting information related to the impact of cooperative learning and participation in group workshops on improving drawing skills, -The study found that there were statistically significant differences between the average scores of the experimental and control groups in the level of drawing skills for middle school students after using cooperative learning and participation in group workshops (posttest) in favor of the experimental group in the posttest, as the use of cooperative learning and participation in group workshops succeeded in Improving drawing skills for middle school students, which demonstrates the incorrectness of the study’s first sub-hypothesis, which states that “there is no relationship with a significant effect between the use of cooperative learning and participation in group workshops on improving drawing skills for middle school students,” which explains the effectiveness and success of using learning. Collaborative and participation in group workshops to improve drawing skills for middle school students Therefore, the study recommends the need to pay attention to providing training programs and courses for students to teach them how to benefit from workshops and cooperative education to increase their abilities and skills.
Keywords: cooperative education - participation in group workshops - improving drawing skills - middle school students.